The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/pros.21457
|View full text |Cite
|
Sign up to set email alerts
|

Chronic prostatitis does not influence urinary PCA3 score

Abstract: In this study, NIH II and III chronic prostatitis did not influence the PCA3 score. Our results suggest that increased PCA3 score is unlikely to be explained by the sole chronic prostatitis and warrants prostate biopsies to eliminate prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 26 publications
3
18
0
3
Order By: Relevance
“…In the first published study on the measure of the PCA3 score in patients with indication of PCa (serum PSA level 43 ng/ml), up to 37% of the 108 tested patients were diagnosed with chronic prostatitis [11]. Their median PCA3 score was not different from that of men with normal histology, and it was concluded that both kinds of patients could be grouped in a unique population of patients without cancer; similar results were obtained in other studies [12][13][14].…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the first published study on the measure of the PCA3 score in patients with indication of PCa (serum PSA level 43 ng/ml), up to 37% of the 108 tested patients were diagnosed with chronic prostatitis [11]. Their median PCA3 score was not different from that of men with normal histology, and it was concluded that both kinds of patients could be grouped in a unique population of patients without cancer; similar results were obtained in other studies [12][13][14].…”
Section: Introductionsupporting
confidence: 80%
“…In a prospective study, aiming to evaluate the effect of chronic prostatitis on the PCA3 score, this biomarker was o35 in all patients with a negative biopsy [11]. This suggests that the PCA3 score could be a valuable tool in patients with elevated PSA levels and indication of chronic prostatitis/BPH, to distinguish those subjects who will benefit from prostate biopsy [11][12][13][14]. According to Vlaeminck-Guillen et al [14], an increased PCA3 score in these patients is unlikely related to chronic prostatitis/BPH, representing an additional reason for performing a biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 38 men that had either urethritis, chronic prostatitis (bacterial or abacterial) or prostadynia, all patients had a urinary PCA3 score of ≤28, suggesting that infection and/ or inflammation did not increase urinary PCA3 levels. 48 Finally, the TMPRSS2-ERG fusion occurs at a variable frequency (16-50%) in patients of different ethni cities with prostate cancer, which might decrease the sensitivity of this test in reallife patient populations. 49 Alterations in DNA methylation Development of prostate cancer is associated with alter ations in tissue of a histologically normal appearance within the peripheral zone, termed a field effect, that occur both as a peritumour response, as well as a change distant from tumour foci.…”
Section: Key Pointsmentioning
confidence: 99%
“…La principale limite de cette étude est l'absence de précision sur la nature de la prostatite. Une étude récente a de fait évalué le score PCA3 chez 34 patients avec prostatite chronique documentée [56]. Le diagnostic de prostatite chronique, basé sur des éléments cliniques, a été affiné par la réalisation d'une version simplifiée du test des quatre verres de Meares-Stamey.…”
Section: Le Test Urinaire Pca3 Dans Les Prostatitesunclassified
“…Ce test comprend un massage prostatique qui peut être assimilé au toucher rectal standardisé nécessaire avant le prélèvement urinaire destiné au test PCA3 [10]. Dans l'étude, que les patients aient une prostatite chronique bactérienne (prostatite de type II), une prostatite chronique abactérienne (prostatite de type IIIa) ou une prostatodynie non inflammatoire (stade IIIb), le score urinaire PCA3 était toujours négatif (≤ 28, en moyenne à 9 ± 7, extrêmes : 1 à 28) [56]. Dans la prostatite aiguë, peu de données sont disponibles.…”
Section: Le Test Urinaire Pca3 Dans Les Prostatitesunclassified